MITOS MENJADI BATU DALAM CERITA RAKYAT KALIMANTAN TENGAH : SEBUAH KAJIAN STRUKTURALISME LEVI STRAUSS - Titik Wijanarti (Balai Bahasa Sulawesi Tengah, 2013)
Indonesian folklore are varied in the regional languages. Those folklore, however, have similar patterns as well as different patterns. One of the similar patterns that can be found in the Indonesian Folklore is the phenomenon of the characters turning into a stone. This research is aimed to elucidate the meaning of the phenomenon in the folklore. Based on the analysis of LeviStrauss’stucturalism to the folklore of central Kalimantan, it is concluded that the change of the character turning into a stone is a symbol of calamity as a results of breaking the rules and life norms.